RESPONSE OF HYPOTHYROIDISM TO HOMEOPATHIC TREATMENT: A REPORT OF THREE CASES - DOGRA, SOUMYABRATA; MANDAL, PRATIMA (Innovare Journal of Medical Sciences, 2020)
Objectives:Hypothyroidism is a disease in which the thyroid gland does not produce enough thyroid hormone.It is the second most common endocrine disorder among women.Common causes are autoimmune disease such as Hashimoto’s thyroiditis, surgical removal of the thyroid and radiation therapy.Symptoms of Hypothyroidism include weight gain, alteration in cognition, fatigue, infertility and menstrual abnormalities.Thyroid stimulating hormone is highly sensitive to thyroid dysfunction and is used to evaluate thyroid disorders.Monotherapy with Levothyroxine is the standard for treating hypothyroidism in the conventional method.Apart from coventional method of treatment homoeopathy also has a scope in the treatment of hypothyroidism. Methods: This is a series of three cases which presented with symptoms of Hypothyroidism thoroughly evaluated and treated with constitutional homoeopathic medicine in a variable period of time.Assesment of thyroid stimulating hormone was done to see the improvement in the cases . Results: A marked improvement in the clinical symptoms as well as the pathological report was observed. Conclusion: This case series shows that Homoeopathic intervention can be used in the treatment of Hypothyroidism.